Bridging the Gap: Navigating the Nexus of Tuberculosis and Mental Well-being - Raja Danasekaran (Indian Journal of Community Medicine)
The article explores the intricate relationship between tuberculosis (TB) and mental health, emphasizing the bidirectional impact and implications for healthcare strategies. The global burden of TB, coupled with psychosocial challenges, necessitates integrated care. Challenges like stigma and fragmented healthcare demand innovative solutions. The review highlights the interconnected nature of mental health and TB treatment outcomes, showcasing promising interventions from psychosocial support to evidence-based approaches. Persistent challenges require ongoing advocacy. Future research should delve into specific mental health conditions and TB outcomes. Recent reviews stress interdisciplinary collaboration, policy changes, and technology for accessible and patient-centric care. This review contributes insights to address TB and mental health globally, promoting a unified, patient-centered approach for sustainable healthcare.